Trademark Cancellation of The PT. DIPOSIN in The Principle of Legal Certainty by Sudikno Mertokusumo - Risma Nur Arifah; Azlin Alisa Ahmad; Silvana Oktavia Rochmawati (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
Trademark cancellation can be done by registered trademark owners, such as PT. Pos Indonesia filed a trademark cancellation suit against the DIPOSIN mark because the mark has similarities in principle to the Pos Indonesia mark and its registration was carried out in bad faith. The judge granted the lawsuit for the cancellation of the DIPOSIN mark in part and the cancellation decision was not implemented. So, because of this, there is a legal inconsistency that results in the absence of legal certainty for brand owners who have good intentions. This study aims to discuss the judges' considerations in Decision number 8/Pdt.Sus-HKI/Merek/2020/PN.Niaga.Sby and the application of the principle of legal certainty according to Sudikno Mertokusumo. This research is normative legal research using statutory, conceptual, and case approaches. This research shows that based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications the judge's consideration in Decision Number 8/Pdt.Sus-HKI/Merek/2020/PN.Niaga.Sby is appropriate however, the implementation of the decision to cancel the trademark is not appropriate with what has been set. This decision gave rise to an inconsistency of norms which resulted in the absence of legal certainty for brand owners. According to Sudikno Mertokusumo, for the law to function in a real way, the law must be upheld, because then the law becomes a reality and the law must reflect legal certainty, benefit, and justice.